2020
DOI: 10.5935/1518-0557.20200017
|View full text |Cite
|
Sign up to set email alerts
|

Taurine effects on Bisphenol A-induced oxidative stress in the mouse testicular mitochondria and sperm motility

Abstract: Objectives: This study was performed to investigate the protective effects of taurine (2-aminoethanesulfonic acid, TAU) on oxidative stress in the isolated mouse testicular mitochondria, mitochondrial membrane potential (MMP), viability and motility of the exposed sperms to the BPA. Methods: We treated epididymal spermatozoa obtained from mice and isolated mouse testicular mitochondria with BPA (0.8 mmol/mL) and various doses of TAU (5, 10, 30 and 50 µmol/L). We used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
4
23
0
Order By: Relevance
“…These results are supported by the study of Rezaee-Tazangi et al that reported that isolated mice testicular mitochondria treated with 800 µM BPA have significantly higher levels of ROS, malondialdehyde (MDA), and mitochondrial membrane potential (MMP) than the control, as well as reduced SOD and glutathione (GSH) levels [130]. Moreover, BPA considerably impaired epididymal sperm motility and viability, possibly due to the triggering of OS [130]. Indeed, in vitro exposure of human spermatozoa to BPA resulted in mitochondrial dysfunction (decreased MMP and increased mitochondrial generation of O2-) with a consequent reduction in sperm motility and increased DNA oxidative damage [106].…”
Section: Impact Of Bpa Exposure On Oxidative Stress In Testis and Spermsupporting
confidence: 56%
See 3 more Smart Citations
“…These results are supported by the study of Rezaee-Tazangi et al that reported that isolated mice testicular mitochondria treated with 800 µM BPA have significantly higher levels of ROS, malondialdehyde (MDA), and mitochondrial membrane potential (MMP) than the control, as well as reduced SOD and glutathione (GSH) levels [130]. Moreover, BPA considerably impaired epididymal sperm motility and viability, possibly due to the triggering of OS [130]. Indeed, in vitro exposure of human spermatozoa to BPA resulted in mitochondrial dysfunction (decreased MMP and increased mitochondrial generation of O2-) with a consequent reduction in sperm motility and increased DNA oxidative damage [106].…”
Section: Impact Of Bpa Exposure On Oxidative Stress In Testis and Spermsupporting
confidence: 56%
“…More recently, using an in vitro experimental model, Rahman and colleagues showed that mice spermatozoa exposed to 100 µM BPA for 6 h have a significant decrease in the percentage of motile spermatozoa and intracellular ATP levels, increased activity of protein kinase-A (PKA), tyrosine phosphorylation and ROS levels [129]. These results are supported by the study of Rezaee-Tazangi et al that reported that isolated mice testicular mitochondria treated with 800 µM BPA have significantly higher levels of ROS, malondialdehyde (MDA), and mitochondrial membrane potential (MMP) than the control, as well as reduced SOD and glutathione (GSH) levels [130]. Moreover, BPA considerably impaired epididymal sperm motility and viability, possibly due to the triggering of OS [130].…”
Section: Impact Of Bpa Exposure On Oxidative Stress In Testis and Spermmentioning
confidence: 69%
See 2 more Smart Citations
“…Since the increase in ROS (reactive oxygen species) is one of the recognized effects of BPA in male spermatogenesis, causing reduction in sperm viability and motility, due also to mitochondrial dysfunction, a study explored the efficacy of taurine in reversing such events, although not properly epigenetic changes, observing good results in a dose-dependent fashion (71). N-Acetylcysteine also has been evaluated to reduce ROS after BPA exposure, showing amelioration of sperm motility (36).…”
Section: Discussionmentioning
confidence: 99%